The Protohermes latus species group (Megaloptera: Corydalidae), with description of two new species from India and Myanmar - Liu, Xingyue; Hayashi, Fumio; Yang, Ding (Zootaxa, 2013)
The Protohermes latus species group is recognized by the sexual dimorphism of the adult pronotum and the male genitalia which possess a bilobed ectoproct. Protohermes sonus sp. nov. from northwestern Myanmar and Protohermes sublunatus sp. nov. from northeastern India are herein described as new species placed in the P. latus group. The potential for peculiar behaviour during courtship of the species in the P. latus group is also discussed based on some remarkable morphological features.